Penerapan Manajemen Kinerja pada Sd Negeri 005 Tanjungpinang Kota - Noviyani, Riski Tri; Ricnaldi, Ricnaldi; Adriyanti , Syeila; Satriadi, Satriadi (Sahabat Publikasi, 2024)
This study examines the Application of Performance Management in SD Negeri 005 Tanjungpinang Kota with the development of quality education. Performance management is not only an administrative framework, but also an important foundation for improving the quality of education that governs educational standards and resource management in schools. This study uses a qualitative approach by collecting data in the form of direct interviews with school principals, and morning vice principals who are also teachers and as parties who carry out direct performance management. The purpose of this study is to determine the application of Performance Management as there is at SD Negeri 005 Tanjungpinang Kota in planning, implementing, monitoring, assessing and evaluating, as well as providing constructive feedback. The results of the study that the implementation of performance management has met expectations and can be said to be good, however, to be able to further improve and maintain the quality of quality education, it is still necessary to improve performance in schools in meeting better educational standards.